Divergent Effects of Neutrophils on Fas-Induced Pulmonary Inflammation, Apoptosis, and Lung Damage. Issue 2 (February 2017) - Bruns, Bastian; Hönle, Theresia; Kellermann, Philipp; Ayala, Alfred; Perl, Mario
Abstract : ABSTRACT: Pulmonary Fas activation is essential in the pathogenesis of the acute respiratory distress syndrome. It remains unclear whether Fas-induced lung injury is dependent on neutrophils or mainly triggered by epithelial cell apoptosis. The contribution of lung epithelial cells (LEC) and alveolar macrophages (AM) remains elusive. Mice were neutrophil reduced prior to intratracheal instillation of Fas-activating (Jo2) or isotype antibody for 6 or 18 h. LEC and AM were incubated with Jo2 and in the presence of nuclear factor kappa B, p-38 mitogen activated protein kinase (p38MAPK), or extracellular signal regulating kinase 1/2 (ERK1/2) inhibitors. Cytokines were assessed by cytometric bead array or ELISA. Apoptosis was quantified via active caspase-3 Western blotting and Terminal Deoxynucleotide Transferase dUTP Nick End Labeling (TUNEL). Lung injury was assessed by bronchoalveolar lavage fluid (BALF) protein concentration and lung histology. KC, IL-6, and MCP-1 were markedly increased in lung, plasma, and BALF 18 h after Jo2 in the presence of neutrophils; in neutrophil-reduced mice lungs, MCP-1, but not KC or IL-6, was even further enhanced. Six hours after Jo2, BALF protein was markedly increased only in the presence of neutrophils. Apoptosis remained unaffected by neutrophil reduction. AM released MCP-1 and underwent apoptosis at lower concentrations of Jo2 than LEC. Inhibition of p38MAPK significantly increased, while inhibition of ERK1/2 reduced AM and LEC apoptosis. In conclusion, neutrophils are a necessary component of Fas-induced lung damage, while not affecting lung apoptosis directly per se. LEC display higher resistance to Fas-triggered inflammation and apoptosis than AM.